Improving spectrum management for satellite communication systems with hunger marketing - Li, Feng (2020)
Efficient spectrum management is an important issue in satellite communications due to the pervasive growth in wireless communications and the ever-increasing demand by bandwidth-hungry mobile applications. While various kinds of static and dynamic spectrum allocation schemes have been studied by satellite researchers, the issue of unpredictable user behavior, hence demand for bandwidth, remains one of the key challenges faced by the research community. In this letter, we introduce the hunger marketing strategy in satellite spectrum management in order to address the unpredictable user demands. When adopting hunger marketing, the system always maintain a certain level of spectrum supply shortage, thus stimulating the desire of users to plan and commit their bandwidth requirements in advance, hence making their behavior more predictable and benefiting satellite systems. Besides, in circumstances of multibeam satellite systems, when allocating bands to new satellite users, the issue of increase in inter-cell interference is also considered in this letter. Thus, a two-stage dynamic game model based on hunger marketing is proposed which aims to achieve an optimal balance between spectrum utilization and inter-cell interference. Numerical results are presented to show the effectiveness of the proposed method.